MODEL PENINGKATAN KINERJA SUMBER DAYA MANUSIYANG BERBASIS PADA KOMPETENSI PROFESIONAL, PENDIDIKAN DAN PENGALAMAN - Anniek Rufaida (Jurnal Riset Bisnis Indonesia, 2015)
This study aims to examine, describe, and analyze the effect of experience and education toprofessional competencies; to examine, describe, and analyze the effect of education, experienceand professional competencies to the performance of human resources; and to develop a frameworkof increasing human resources performance based on professional competence, education, andexperience. Census method was carried out as the sampling methods.There were 57 subjects, allsubjects were civil servants. The analysis was performed to test the validity of hypothesis using pathanalysis from Statistical Package for the Social Sciences (SPSS) software. The result showedthat: higher education leads to better performance of human resources; more experienceleads to better performance of human resources; higher professional competence leads to betterperformance of human resources; higher education leads to the higher professional competencies;and more experience leads to higher professional competencies.Keyword : Human resources performance, education, experience and professional competencies.